Field output correction factors and electron fluence perturbation of the microSilicon and microSilicon X detectors. (21st April 2022) - Delbaere, Alexia; Younes, Tony; Simon, Luc; Khamphan, Catherine; Vieillevigne, Laure
Abstract: Objective. The aim of this study was to determine field output correction factors k Q clin, Q ref f clin, f ref and electron fluence perturbation for new PTW unshielded microSilicon and shielded microSilicon X detectors. Approach. k Q clin, Q ref f clin, f ref factors were calculated for 6 and 10 MV with and without flattening filter beams delivered by a TrueBeam STx. Correction factors were determined for field sizes ranging from 0.5 × 0.5 cm 2 to 3 × 3 cm 2 using both experimental and numerical methods. To better understand the underlying physics of their response, total electron (+positron) fluence spectra were scored in the sensitive volume considering the various component-dependent perturbations. Main results. The microSilicon and microSilicon X detectors can be used down to the smallest studied field size by applying corrections factors fulfilling the tolerance of 5% recommended by the IAEA TRS483. Electron fluence perturbation in both microSilicon detectors was greater than that in water but to a lesser extent than their predecessors. The main contribution of the overall perturbation of the detectors comes from the materials surrounding their sensitive volume, especially the epoxy in the case of unshielded diodes and the shielding for shielded diodes. This work demonstrated that the decrease in the density of the epoxy for the microSilicon led to a decrease in the electron fluence perturbation. Significance. A real improvement was observed regarding the design of the microSilicon and microSilicon X detectors compared to their predecessors.